Examining Primary Education Students’ Expertise Concerning the Environmental Impact of Economic Activities and Environmental Catastrophes (Training and Practice : Journal of Educational Sciences, 2021)
This study is concerned with the knowledge on mining, industrial and other economic activities, as well as different environmental disasters affecting the region of Hungary. Students majoring in primary school teaching participated in the research. Through questionnaires, I examined the hypothesized importance of teaching children about the environmental impact of economic activities and environmental disasters in their geography lessons, and I analyzed the results via Fisher and McNemar tests in SPSS. Based on these data we can conclude that there is no correlation between primary education students’ previously gained knowledge concerning the detrimental environmental effects of economic activities, and their current motivation in discussing such topics in geography lessons. The conclusion remains valid for environmental disasters as well.